Antioxidative and anti-inflammatory effects of Thai traditional topical herbal recipe for osteoarthritis of knee - Junlatat, Jintana; Nusawat, Suphannachat; Sangprapai, Warinee; Chaweerak, Saran (Health Science, Science and Technology Reviews, 2022)
The purpose of the study was to evaluate the anti-oxidative and anti-inflammatory effects of a Thai traditional topical herbal recipe for osteoarthritis of knee (OA knee). This recipe has been used to treat and relieve pain and swelling around the knee, it was called Pok-Kao recipe (PK) in Thai. The recipe was prepared, extracted by maceration with 50%ethanol and then freeze-dried to obtain the extract (PKE). PKE was tested for anti-oxidation using DPPH, FRAP and ABTS assays. Anti-inflammatory mechanisms of PKE were investigated by measuring nitric oxide (NO) production using Griess reagent. In addition, the inflammatory-related gene expression and prostaglandin E2 (PEG2) inhibition level was investigated by reverse transcription-polymerase chain reaction technique (RT-PCR) and enzyme-linked immunosorbent assay (ELISA) in LPS-stimulated macrophages RAW264.7 cells. The results found that PKE extract showed anti-oxidant activity when tested by using DPPH assay (EC50 was 674.90±27.00 µg/ml), FRAP assay (14.03±2.45 µg Trolox equiv./mg) and ABTS assay (EC50 was 31.01±7.19 µg/ml). Besides, the extracts exhibited the anti-inflammatory effect at doses 50-200 µg/ml which inhibited the NO production and the expression of cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) in the cells. And, the extract strongly inhibited the PGE2 production (EC50 was 18.97 µg/ml). The results support the traditional uses of this recipe for treating OA knee and are particularly useful for product development.